Linking TPPII to the protein interaction and signalling networks. (August 2020) - Nahálková, Jarmila
Graphical abstract: Highlights: The identification of the molecular mechanisms driving TPP2 interaction network. Adaptive and innate immunity (ID, Kit Receptor, BCR, IL-2, G-CSF and NFκB signalling). Aerobic glycolysis (ID and IL-2 signalling). Tumorigenesis (TGF- β and p53 signalling; MAPKs; the control of mTOR). Potential functional link to lung cancer pathology. Abstract: Tripeptidyl peptidase II (TPPII) is primarily considered a house-keeping exopeptidase, which contributes to the functions of the ubiquitin-proteasome system by the maintenance of the cellular amino acid homeostasis. Although functionally well-characterised in vitro and using the mammalian cell models, less is known about the molecular mechanisms of its involvement in the signalling and metabolic pathways, which mediate its cellular functions. The present protein-protein interaction network analysis identified these mechanisms involved in the adaptive and innate immunity, the metabolism of the glucose, cancer cell growth, apoptosis, cell cycle and DNA damage responses. The interaction network constructed based on the publicly available protein-protein interaction data was extended by the application GeneMania, which was further used for the pathway enrichment, the protein function prediction and the protein node prioritisation analysis. The analysis suggested that the molecular mechanisms linked to the adaptive and innate immunity (ID, Kit receptor, BCR, IL-2 and G-CSF signalling; the regulation of NFκB), the aerobic glycolysis (ID and IL-2 signalling), tumorigenesis (TGF- β and p53 signalling; the top priority nodes MAPKs, mTOR regulation), diabetes (Kit receptor signalling; the top priority node GSK3 β ) and neurodegeneration (the control of mTOR and A β peptide degradation) are controlling the resulting TPPII interaction network. The uncharacterized interactions with two lung cancer suppressors (DOK3, DENND2D), a protein involved in the increased risk of the lung cancer in smokers (CYP1A1) and a protein implicated in asthmatic reactions (CHIA) suggest potential roles of TPPII in the lung cancer pathology. The interactions with methyltransferase CARNMT1, which modifies di- and tripeptides and the xenobiotic processing enzyme CYP1A1, are additional candidates for the breakthrough in new functions discovery of TPPII.